Fruit and vegetable intake and mental health among family caregivers of people with dementia in Uganda - Herbert, E. Ainamani; Wilson, M. Bamwerinde; Godfrey, Z. Rukundo; Sam, Tumwesigire; Valence, Mfitumukiza; Everd, Bikaitwoha Maniple; Alexander, C. Tsai (Elsevier GmbH, 2022)
Consumption of fruits and vegetables is correlated with improved mental wellbeing. Although this growing body of research has been recognized by researchers and clinicians in high-income countries, fewer studies examining this relationship have been conducted in low- and middle-income settings. In this study, we sought to estimate the association between fruit and vegetable intake and symptoms of depression and anxiety. We conducted a cross-sectional study among 242 family caregivers of people with dementia in southwestern Uganda. Fruit and vegetable intake in the past week was measured with a food frequency questionnaire. Depression and anxiety were assessed using the depression and anxiety subscales of the 42-item Depression, Anxiety and Stress Scales. Multivariable regression models were used to estimate the associations between fruits and vegetable consumption and depression and anxiety, adjusting for caregiving burden and other potential confounders. Depression symptom severity was negatively associated with consumption of jackfruits (b =-4.68; 95% confidence interval [CI], -8.96 to -0.39), green leafy vegetables (b =-14.1; 95% CI, -18.0 to -10.1), root vegetables (b =-14.0; 95% CI, -19.5 to -8.63), and other vegetables (b =-14.8; 95% CI, -19.3 to -10.3), and frequent consumption of vegetables (b =-1.91; 95% CI, -3.77 to -0.04). Anxiety symptom severity was negatively associated with consumption of green leafy vegetables (b =-12.2; 95% CI, -16.0 to -8.46), root vegetables (b=-12.6; 95% CI, -17.5 to -7.58), and other vegetables (b =-12.7; 95% CI, -17.0 to -8.40), and frequent consumption of vegetables (b =-2.07; 95% CI, -3.84 to -0.29). Our results suggest that fruit and vegetable consumption is associated with reduced depression and anxiety symptoms.